Raising Mental Illness Awareness Among Students Of Higher Education Institutions Through Advertising Campaign Strategy - Jamadil Azrul, Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2020)
The objective of this study is to identify the main mental illness issues among higher education students. It is also analyze the effectiveness of advertising campaign strategy among Higher Education Institutions student. Based on that, video advertisement campaign about depression is created. Besides, students of higher education will expose about depression and seek help if they are having any of its symptoms.